Peningkatan Literasi Kesehatan Masyarakat melalui Edukasi Gizi dan Pemeriksaan Kesehatan di Desa Kayutanyo, Kabupaten Banggai: Enhancing Community Health Literacy through Nutritional Education and Health Screenings in Kayutanyo Village, Banggai Regency - Wijianto, Wijianto; Hasan, Sri Musriawati; Muhammad, Hana Yulianti; Dg. Mangemba; Adhyanti (Jurnal Pengabdian Masyarakat: Svasta Harena, 2025)
Kayutanyo Village, East Luwuk District, Banggai Regency, is an area with high potential risk for Non-Communicable Diseases (NCDs) triggered by unhealthy consumption patterns and lifestyles, and exacerbated by the characteristics of NCDs which are asymptomatic and have minimal clinical symptoms, so that they are often not recognized by the community. This community service activity aims to improve public health literacy through nutrition education, early detection of nutritional status and blood sugar level checks. The implementation method consists of anthropometric examinations, blood sugar level checks, and health education delivered interactively to the community. The results of the examination showed that 44.9% of participants had blood sugar levels above normal limits, while 39.2% of participants were overweight or obese. These findings indicate the need for sustainable community-based interventions in promotive and preventive efforts against NCDs. The education provided was responded to positively by the community and increased understanding of the importance of a balanced diet and regular health checks. This activity is expected to be an initial model that can be replicated in other areas with similar characteristics.